Smartphone Apps Provide a Simple, Accurate Bedside Screening Tool for Orthostatic Tremor. Issue 6 (8th October 2017) - Bhatti, Danish; Thompson, Rebecca; Hellman, Amy; Penke, Cynthia; Bertoni, John M; Torres‐Russotto, Diego
Abstract: Background: Orthostatic Tremor (OT) is characterized by the presence of a sensation of instability while standing, associated with high frequency (13–18 Hz) lower extremity tremor. Diagnosis is confirmed with surface electromyography (EMG). An accurate screening tool that could be used in the routine clinical setting, without any specialized equipment, would be useful in earlier detection of OT and judicial use of additional testing. Objective: The objective of this study was to evaluate OT diagnostic test characteristics at bedside using iPhone's built‐in accelerometer and available applications for tremor recordings. Methods: We obtained recordings using iPhones (Model 5, 5s, and 6) and free Applications ("LiftPulse" by LiftLabs [App1] and "iSeismometer" by ObjectGraph LLC [App2]) at default settings. Results: 24 EMG‐confirmed OT subjects (mostly females, 22/24) and 15 age‐matched controls (mostly males, 11/15) were evaluated. App1 detected OT range tremor in 22/24 patients and none of the controls. (Sensitivity = 92%, Specificity = 100%, NPV = 88%). App2 detected OT range tremor in 21/24 patients and in 1/13 controls (Sensitivity = 88%, Specificity = 92%, NPV = 80%). When combined, 24/24 patients and 1/13 controls had OT range tremor (Sensitivity = 100%, Specificity = 92%, NPV = 100%). Conclusions: Smartphone apps that use the built‐in accelerometer provide a simple, accurate and inexpensive bedside screening diagnostic tool for patients with OT.